The Influence of Learning Arabic on Memorizing the Qur'an for Darul Qur'an Al Waafa Bogor High School Students - Laode Munawan; AB. Musyafa Fathoni; Anip Dwi Saputro (Universitas Muhammadiyah Ponorogo, 2022)
This research is useful for knowing the level of Arabic language proficiency, memorization ability of the Quran by students, and determining the extent of the influence of Arabic language learning on Quran memorization of students at SMA Darul Qur'an Al Wafa Bogor. The research is quantitative and aims to test hypotheses. Data collection methods include questionnaires, interviews, and documentation. Data analysis involves inferential descriptive statistics and simple regression analysis. Arabic language learning at SMA Darul Qur'an Al Wafa Bogor is at a very good level. Various methods (eclectic methods) are used in the learning activities, including using two books, Silsilah Ta'lim al Lughah al Arabiyah and Al Muwajjih. The research findings demonstrate the influence of Arabic language learning on Quran memorization among students at SMA Darul Qur'an Al Wafa Bogor. This is supported by the analysis result of the t-value of 3.930, which has a significance value of 0.000, lower than the predetermined significance value of 0.05. The coefficient of determination, at 28.9%, indicates a positive influence, meaning that as students' Arabic language learning increases, so does their Quran memorization. The remaining 71.1% of factors affecting the Y variable were not examined by the researcher.